2016
DOI: 10.1002/ajmg.b.32415
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder traits inSlc9a9knock‐out mice

Abstract: Autism spectrum disorders (ASDs) are a group of neurodevelopmental disorders which begin in childhood and persist into adulthood. They cause lifelong impairments and are associated with substantial burdens to patients, families, and society. Genetic studies have implicated the sodium/proton exchanger (NHE) nine gene, Slc9a9, to ASDs and attention-deficit/hyperactivity disorder(ADHD). Slc9a9 encodes, NHE9, a membrane protein of the late recycling endosomes. The recycling endosome plays an important role in syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…Receptor-mediated endocytosis of holo-transferrin is the canonical physiological mode of iron delivery to cells (2). Electrochemical potential (E 0 ) of transferrin iron complex is too negative, and acidification of endosomal lumen has been sug- MARCH 10, 2017 • VOLUME 292 • NUMBER 10 gested to make the E 0 more positive (29). Thus, a drop in the pH caused by proton influx via V-ATPase in the sorting endosomes could lead to release of iron from holo-transferrin-TfR complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptor-mediated endocytosis of holo-transferrin is the canonical physiological mode of iron delivery to cells (2). Electrochemical potential (E 0 ) of transferrin iron complex is too negative, and acidification of endosomal lumen has been sug- MARCH 10, 2017 • VOLUME 292 • NUMBER 10 gested to make the E 0 more positive (29). Thus, a drop in the pH caused by proton influx via V-ATPase in the sorting endosomes could lead to release of iron from holo-transferrin-TfR complex.…”
Section: Discussionmentioning
confidence: 99%
“…Functional evaluation of these autismassociated mutations in astrocytes showed that these cells lose their ability to clear glutamate to a significant extent as a consequence of dysregulated trafficking of glutamate transporter (GLAST) (27). Moreover, global knock-out SLC9A9 mice (Slc9a9 KO) show traits of autism spectrum and attention deficit hyperactivity disorder (29). Thus, by modulating endosomal pH, NHE9 could regulate delivery and recycling of various endocytic cargos, including proteins involved in iron homeostasis.…”
mentioning
confidence: 99%
“…There were differences between the two WKY strains on behavioral parameters such as lower social interest and lower ultrasonic vocalization calls, suggested that the Charles River strain has traits consistent with ASDs (Zhang-James et al, 2014). We also reported that the SLC9A9 knockout mouse showed ASD-like traits as evidenced by significant decreases in ultrasonic vocalization and increases in repetitive behaviors (Lina Yang, 2016). However the SLC9A9 knockout did not produce other relevant ASD features, such as decreased social behavior (Lina Yang, 2016).…”
Section: : Reviewmentioning
confidence: 95%
“…We also reported that the SLC9A9 knockout mouse showed ASD-like traits as evidenced by significant decreases in ultrasonic vocalization and increases in repetitive behaviors (Lina Yang, 2016). However the SLC9A9 knockout did not produce other relevant ASD features, such as decreased social behavior (Lina Yang, 2016). …”
Section: : Reviewmentioning
confidence: 95%
“…A total recording time of 30 min for each rat was divided into six 5-minute segments. 5-Minute segments were chosen based on others and our previous studies to examine locomotor activity and habituation in experimental chambers [51,52]. J Psychiatry Brain Sci.…”
Section: Discussionmentioning
confidence: 99%